Peran Feminisme dalam Strategi Komunikasi Akun Instagram @evtessia - Imay Indari; Ilah, Ilah Holilah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
In the midst of the ever-increasing digital wave, social media has revolutionised the way we communicate, spread ideas and voice our aspirations. Instagram, as one of the leading platforms, is not only a platform for visual expression, but also a strategic arena to spread deep social values. Among them, feminism, as a movement that promotes women's justice and empowerment, finds space to flourish and interact with millions of users around the world. The purpose of this study is to examine the role of feminism in the communication strategy of @evtessia's Instagram account. Using a qualitative approach and content analysis method, this research examines how feminist values are incorporated in the visual and narrative content published by the account. Data was collected by observing the interaction between content uploaded over the past six months with the account and followers. The results of the analysis show that @evtessia consistently translates messages of female consent, gender-specific justice and critique of patriarchy through the use of symbols, colours and texts that reflect a feminist perspective. In addition, the communication strategies implemented also create spatial interactions that support key dialogues on gender equality issues, creating a solid community on the social media platform. The findings are expected to help us understand the role of social media as a tool to support social change and to enhance feminism in the digital age.